2005
DOI: 10.1073/pnas.0504658102
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibody responses drive the evolution of human immunodeficiency virus type 1 envelope during recent HIV infection

Abstract: HIV type 1 (HIV-1) can rapidly escape from neutralizing antibody responses. The genetic basis of this escape in vivo is poorly understood. We compared the pattern of evolution of the HIV-1 env gene between individuals with recent HIV infection whose virus exhibited either a low or a high rate of escape from neutralizing antibody responses. We demonstrate that the rate of viral escape at a phenotypic level is highly variable among individuals, and is strongly correlated with the rate of amino acid substitutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
316
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(345 citation statements)
references
References 69 publications
22
316
1
3
Order By: Relevance
“…To demonstrate this, we further analyzed env sequences sampled through time from two patients with markedly distinct rates of phenotypic escape from nAb responses [31] (patient 01-0083 and patient 01-0127; Figure 4). As in Frost et al [2], we show that the virus that rapidly escaped nAb responses in patient 01-0127 accumulated nonsynonymous substitutions at a considerably higher rate on backbone branches, while synonymous divergence rates appear to be unaffected (similar plots were obtained for internal branches, unpublished data).…”
Section: Author Summarysupporting
confidence: 62%
See 3 more Smart Citations
“…To demonstrate this, we further analyzed env sequences sampled through time from two patients with markedly distinct rates of phenotypic escape from nAb responses [31] (patient 01-0083 and patient 01-0127; Figure 4). As in Frost et al [2], we show that the virus that rapidly escaped nAb responses in patient 01-0127 accumulated nonsynonymous substitutions at a considerably higher rate on backbone branches, while synonymous divergence rates appear to be unaffected (similar plots were obtained for internal branches, unpublished data).…”
Section: Author Summarysupporting
confidence: 62%
“…Our results show that the nonsynonymous rates in the env gene, most likely effecting phenotypic escape from nAbs ( Figure 4, [2]), do not correlate with disease progression in patients harbouring HIV-1 group M viruses. While these conclusions are based on serial sampled data for only two patients, Frost et al [2] have clearly demonstrated this effect in multiple patients. Crucially, we show that the selection pressure on env obscures the expected correlation between overall nucleotide substitution rates and disease progression, emphasizing the need to disentangle the contributions of synonymous and nonsynonymous substitutions to HIV evolution.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Mechanisms of humoral escape include: hiding of critical neutralizing epitopes, extension of gp120 variable loops, conformational protection of viral receptor binding motifs, and extensive glycosylation of envelope surface proteins. It has been demonstrated that acutely infected patients produce NAbs against autologous virus within months of seroconversion (Albert et al 1990, Tremblay and Wainberg 1990, Richman et al 2003, Wei et al 2003, Frost et al 2005), but although the early produced NAbs reach fairly high titers, escape mutants are rapidly selected due to the ongoing viral replication (Richman et al 2003, Wei et al 2003. It also has been shown that chronically HIV-1 infected patients develop NAbs against earlier viral isolates, but they fail to neutralize contemporaneous virus (Albert et al 1990, Tremblay and Wainberg 1990, Skrabal et al 2005).…”
Section: Escapementioning
confidence: 99%